Fiscal Policy, Labor Markets and the Poor. (IMF Working Papers; Working Paper, 1990)
In designing policy measures, including possible social safety nets, targeted to the poor, it is important to fully understand the efficiency implications of these measures. There is abundant macroeconomic literature on their negative effects on the poor's work effort. The literature, however, does not adequately recognize the positive effects of these measures on improved nutrition and health of the poor or on aggregate supply. This paper presents an analytical framework to trace both the positive efficiency implications, as well as the resource (or cost) implications of such policies.